2015
DOI: 10.1182/blood-2014-08-595256
|View full text |Cite
|
Sign up to set email alerts
|

A novel inflammatory pathway mediating rapid hepcidin-independent hypoferremia

Abstract: Key Points• Stimulation of Toll-like receptors 2 and 6 reduces ferroportin expression in mouse macrophages by hepcidin-independent mechanism(s).• Reduced expression of ferroportin in macrophages that recycle iron from red cells is sufficient to rapidly induce hypoferremia in mice.Regulation of iron metabolism and innate immunity are tightly interlinked. The acute phase response to infection and inflammation induces alterations in iron homeostasis that reduce iron supplies to pathogens. The iron hormone hepcidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
134
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(142 citation statements)
references
References 52 publications
3
134
0
5
Order By: Relevance
“…Previous studies with infection models have shown hepcidin induction occurring during the first 12 h of infection (64), and the moderate change we observe is after the time window at which the hepcidin transcripts increase. The notable decrease in FPN mRNA suggests that hepatic iron regulation at this time point may also involve additional hepcidin-independent pathways that involve transcriptional regulation of FPN (65,66). The mRNA levels of TfR appear unchanged while DMT1 mRNA levels are reduced in the infected mice compared with the mockinfected mice.…”
Section: Icl-1 Visualizes Changes In Labile Iron Pools In An a Baumamentioning
confidence: 81%
“…Previous studies with infection models have shown hepcidin induction occurring during the first 12 h of infection (64), and the moderate change we observe is after the time window at which the hepcidin transcripts increase. The notable decrease in FPN mRNA suggests that hepatic iron regulation at this time point may also involve additional hepcidin-independent pathways that involve transcriptional regulation of FPN (65,66). The mRNA levels of TfR appear unchanged while DMT1 mRNA levels are reduced in the infected mice compared with the mockinfected mice.…”
Section: Icl-1 Visualizes Changes In Labile Iron Pools In An a Baumamentioning
confidence: 81%
“…In light of this, we examined expression patterns of other genes involved in iron utilization or in the inflammation pathway (reviewed by Ganz, 2011;Ginzburg and Rivella, 2011;Guida et al, 2015;Kim and Nemeth, 2015;Li et al, 2014;Nagata, 2007;Rivella, 2015;Yoshida et al, 2005b) to address indirect or Nan-KLF1-independent causes for the inefficient erythropoiesis (Gillinder et al, 2016). Expression is either unchanged [hemochromatosis (Hfe), IRP1 (Aco1), aconitase (Aco2), Flvcr1 (Mfsd7b); Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As a further variable, Vitamin D is an important suppressor of hepcidin, and dogs with severe CE have been shown to have reduced vitamin D concentrations (Gow et al, 2011;Bacchetta et al, 2014). Moreover, in inflammatory conditions, the action of metal transporters can be disrupted, independently of hepcidin (Guida et al, 2015). In human IBD, active disease was seen to correlate with decreased mucosal DMT1 expression (Wu et al, 2015).…”
Section: Inclusion Criteriamentioning
confidence: 99%